18 CHROMIUM'S EFFECT ON INSULIN SENSITIVITY IN HIV DISEASE (PILOT STUDY). (1st March 2005) - Ferris, R.; Yu, G. Q.; Kelly, P.; McNurlan, M.; Mynarcik, D.; Gelato, M.
Abstract : Purpose: The purpose of this study is to investigate the effect of chromium picolinate supplementation on insulin sensitivity in HIV disease. Methods: The study consisted of six HIV-positive patients (3 female; 3 male) with insulin resistance (IR) determined by a hyperinsulinemic-euglycemic clamp. Insulin sensitivity was determined as the rate of infused glucose necessary to maintain euglycemia during an infusion of insulin (Rd). Subjects were infused with 1.2 mU insulin/kg body weight per minute to elevate plasma insulin levels to ˜ 40 microU/mL, sufficient to suppress hepatic glucose production in other insulin-resistant states. Dextrose was administered intravenously at variable rates to maintain plasma glucose at 90 mg/dL. Plasma glucose was assessed from arterialized blood, obtained by the heated hand technique. Insulin resistance was determined between the second and third hour of insulin infusion. Plasma glucose was determined by the glucose oxidase method. To normalize for differences in body composition, insulin sensitivity is expressed as mg glucose/kg lean body mass (LBM) per minute. Lean body mass was determined by dual-energy x-ray absorptiometry (DEXA) performed with a total body scanner. Patients with an Rd<6 received 1000 μg of chromium picolinate once a day for 8 weeks. The hyperinsulinemic-euglycemic clamp was then repeated to determine Rd post chromium picolinate. Results: Insulin sensitivity significantly increased after 8 weeks of chromium picolinate (p<0.04, paired t-test). Five subjects showed 20% or greater improvement in Rd after chromium supplementation. Half the subjects had>40% improvement in Rd. One subject's insulin sensitivity was unchanged post-chromium. Conclusion: Supplementation with chromium picolinate may improve insulin sensitivity in HIV disease. Further study is required. (Table )